Emergency Department Visits for Postpartum Complications [23J]. (May 2016) - Brousseau, Erin C.; Danilack, Valery A.; Cai, Fei; Yang, Unikora; Matteson, Kristen A.
Abstract : INTRODUCTION: Most estimates of the prevalence and types of postpartum complications are based on hospital readmissions. However, using hospital readmissions (which occurs in only 1–2% of postpartum women) is problematic as it fails to include women with postpartum complications assessed in the office or emergency department (ED). We utilized data from a cohort of women evaluated in an ED setting to better characterize complications experienced by women in the postpartum period. METHODS: We performed a retrospective analysis of all postpartum visits to the ED at a tertiary care women's hospital over a six-month period. We described characteristics of the population and clinical details of the ED visit, specifically the presenting complaint and final diagnosis. RESULTS: Among 4, 241 deliveries during the study period, 252 women had at least one visit to the emergency department within 42 days after delivery, and the median timing for first visit was 7.5 days postpartum. The most common presenting complaints were wound complication (17.5%), fever (17.1%), abdominal pain (15.9%), headache/dizziness (12.3%), breast problem (10.7%) and hypertension (10.3%). Fifty-seven percent of these visits were by women who delivered vaginally. Sixty-nine percent had at least one maternal co-morbidity, 66% had at least one obstetric complication, and 22% were readmitted to the hospital. CONCLUSION: Women presenting to the ED postpartum period had a wide variety of medical issues but 78% were not admitted. Further research is needed to determine if interventions during hospitalization after delivery can reduce ED visits postpartum, and to evaluate if risk factors for postpartum complications post-discharge can be identified.